Dermatitis by Paederus sp. in the Peruvian Amazon: Report of cases - Fierro-Reinoso, Martin (2018)
In the peruvian amazon we have a great diversity of arthropods which are related to public health problems. For example, there is an unknown beetle of the family Staphylinidae, genus Paederus, capable of producing a caustic-vesicular dermatitis, to anyone who gets any physical contact with its hemolymph. This type of injury has been described in tropical and subtropical areas, causing epidemic outbreaks of seasonal dermatitis throughout the world; as it happened in the weather phenomenon "El Niño" by Paederus irritans (Ciudad de Piura, 1999). We present two dermatitis cases due to Paederus sp. in rural areas of the peruvian amazon, where no cases have been reported earlier.